2000
DOI: 10.1136/ewjm.173.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Pica during pregnancy in low-income women born in Mexico

Abstract: ⅷ Objective To describe pica behavior (ingestion of nonfood items) in pregnant low-income Mexican-born women in Mexico and the United States. ⅷ Design A convenience sample of informants was interviewed with a questionnaire containing open-ended and closed-ended questions. ⅷ Setting A low-income community on the outskirts of Ensenada, Mexico, and clinics serving low-income people in southern California (Santa Ana, Bakersfield, and Los Angeles). ⅷ Participants Of a total of 225 Mexican-born women, 75 (33%) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
53
0
29

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 17 publications
6
53
0
29
Order By: Relevance
“…Pica during pregnancy has been previously documented in both rural and urban parts of the United States, with one study of Mexican American women living in California reporting a 31% prevalence. 22,23 The specific risk factors identified here are consistent with a recent study of predominantly Latino pregnant women in South Central Los Angeles, which found that pica and recent immigration to the United States (as well as low calcium intake) were the strongest predictors of BLLs. 24 There was also some tendency for higher BLLs to be associated with younger maternal age, more advanced EGA, and more recent immigration to the United States.…”
Section: Discussionsupporting
confidence: 88%
“…Pica during pregnancy has been previously documented in both rural and urban parts of the United States, with one study of Mexican American women living in California reporting a 31% prevalence. 22,23 The specific risk factors identified here are consistent with a recent study of predominantly Latino pregnant women in South Central Los Angeles, which found that pica and recent immigration to the United States (as well as low calcium intake) were the strongest predictors of BLLs. 24 There was also some tendency for higher BLLs to be associated with younger maternal age, more advanced EGA, and more recent immigration to the United States.…”
Section: Discussionsupporting
confidence: 88%
“…It appears to be more common in children than in adults, in women than in men, in black people than in white people, in rural areas than in urban areas, and in pregnant women than in non-pregnant women. [4] Pregnant women have been identified as a group in which geophagia is particularly widespread, and studies undertaken in Dar es Salaam (Tanzania) and Nairobi (Kenya) showed prevalences of 64% and 74%, respectively. [5,6] Few studies have described the practice of pica and geophagia in South Africa (SA).…”
mentioning
confidence: 99%
“…[11] While strongly held beliefs about the nutritional benefits and detoxifying effects of geophagia exist, [12] ingestion of soil has been shown to interfere with the bioavailability of micronutrients (leading to micronutrient deficiencies), and may result in geohelminthic infec tions, anaemia, hypokalaemia, peritoneal mesothelioma and intestinal obstruction or perforation. [2,4,8] Geo phagic behaviour may also increase exposure to metal contaminants in the soil, including arsenic and lead -for example, elevated concentrations of arsenic were found in the baked clay (sikor) widely con sumed by pregnant Bangladeshi women in the UK. [3] A study in New York found women who practised pica to have higher blood lead levels than other women.…”
mentioning
confidence: 99%
“…Studies suggest that there are important emotional aspects associated with pica, and this disorder is most often studied in pregnant women because of the risks to baby (Ahmed et al, 2012;Simpson, Mull, Longley, & East, 2000;Thihalolipavan et al, 2013). Inappropriate substances consumed, often toxic (eg.…”
Section: Pica En El Embarazo Y Aspectos Psicologicos Relacionados Resmentioning
confidence: 99%
“…The increasing on synthesis of female hormones could causes mother's body changes and affects the fetal development (Vieira & Parizotto, 2013). These hormonal changes may cause signifi cant physical and psychological changes in women, and result in depressive symptoms, anxiety, poor concentration, irritability, changes in appetite, insomnia, hypersomnia and loss of energy (Vieira & Parizoto, 2013;Simpson et al, 2000).…”
Section: Pica En El Embarazo Y Aspectos Psicologicos Relacionados Resmentioning
confidence: 99%